UniNet a hybrid approach for universal broadband access using small radio cells interconnected by free-space optical links. - Acampora, A. (IEEE Journal on selected areas in communications)
A new type of broadband access system is proposed for providing high-quality, bandwidth-upon-demand telecommunication services to the home and office. Communication terminals attach to the network via short radio links, and users can roam freely within a house or building unencumbered by the availability of wired ?telecommunications outlets?. Basic service is extended through small, high-capacity radio cells; the base stations are interconnected via short, highly focused free-space optical links in a multihop mesh arrangement; and the need for new broadband access cabling is totally surmounted. A tiered arrangement of radio cells further extends service to both out-of-building pedestrian and vehicular users, and service is universally available. Benefits of the approach are described, and issues involving reliability, availability, capacity, and hand off are identified and addressed. Opportunities to refine the basic approach are suggested for further study